Analisis Strategi Komunikasi dan Negosiasi Untuk Meningkatkan Kesuksesan Bisnis - Anindia Jovita Br Ginting; Dwi Rahmadani; Mei Lani Sembiring; Lenti Susanna Saragih; Danny Ajar Baskoro (Student Scientific Creativity Journal, 2024)
Ineffective communication and negotiation can have negative consequences for the company, such as loss of customers, decreased product quality, and decreased trust with customers. Therefore, companies must have effective communication and negotiation strategies to increase business success. This research aims to analyze how communication and negotiation strategies can increase business success. This research uses a descriptive approach with qualitative methods, data collection techniques through literature study. Analyzing data using a qualitative analysis approach, this research concludes that in increasing business success, communication and negotiation strategies play an important role. Effective communication allows companies to interact with customers, partners and other parties more effectively, thereby increasing customer satisfaction, loyalty and business reputation. Meanwhile, good negotiations allow companies to reach profitable agreements with other parties, such as business partners, suppliers and customers. Therefore, companies must have good communication skills to interact with other parties and effective negotiations to reach profitable agreements